Investing for the Old Age : Pensions, Children and Savings - Galasso, Vincenzo; Gatti, Roberta; Profeta, Paola (2012)
In the last century, most countries have experienced both an increase in pension spending and a decline in fertility. We argue that the interplay of pension generosity and development of capital markets is crucial to understand fertility decisions. Since children have traditionally represented for parents a form of retirement saving, particularly in economies with limited or nonexistent capital markets, an exogenous increase of pension spending provides a saving technology alternative to children, thus relaxing financial (saving) constraints and reducing fertility. We build a simple two-period OLG model to show that an increase in pensions is associated with a larger decrease in fertility in countries in which individuals have less access to financial markets. Cross-country regression analysis supports our result: an interaction between various measures of pension generosity and a proxy for the development of financial markets consistently enters the regressions positively and significantly, suggesting that in economies with limited financial markets, children represent a (if not the only) way for parents to save for old age, and that increases in pensions amount effectively to relaxing these constraints.